Enhanced photocatalytic degradation of dye contaminants with TiO2 immobilized on ZSM-5 zeolite modified with nickel nanoparticles. (20th January 2021) - Badvi, Khadije; Javanbakht, Vahid
Abstract: Due to the severe water pollution from effluent dyes, finding a suitable dye degradation technology is needed for the protection of human health and the natural environment. In this work, ZSM-5/TiO2 nanophotocatalysts were successfully prepared by dispersing TiO2 onto the surface of the ZSM-5 zeolite using the sol-gel method, calcinated at different temperatures and then modified with different content of nickel nanoparticle precipitation. The synthesized nanocomposites were systematically characterized and the photocatalytic activity for degradation of methylene blue dye was investigated under UV light irradiation and compared with hydrogen peroxide-assisted photocatalytic degradation, catalytic hydrogen peroxide oxidation, and adsorption processes for dye removal from aqueous solution. Additionally, the effect of various parameters on dye removal like initial pH, initial dye concentration, photocatalyst dose, hydrogen peroxide concentration, nickel content in nanophotocatalyst, calcination temperature, and kinetic investigations were performed. The photocatalytic activity results showed that the incorporation of nickel nanoparticles increased dye degradation efficiency. It was found that hydrogen peroxide-assisted photocatalytic degradation, UV photocatalytic degradation, catalytic hydrogen peroxide oxidation, and adsorption processes were indicated the best results in dye removal, respectively. The highest UV photocatalytic degradation efficiency was obtained for nanophotocatalyst with 0.5% nickel nanoparticle and 600 °C calcination temperature in about 99.80%. Highlights: ZSM-5/TiO2 /Ni nanophotocatalysts were successfully prepared and characterized. The nanocomposite has enhanced photocatalytic degradation of methylene blue. H2 O2 -assisted photocatalytic degradation improved the dye removal efficiency.